The use of wide-bandgap CuCl on silicon for ultra-violet photonics - Bradley, Louise; O'Reilly, Lisa; Natarajan, Gomathi; McNally, Patrick; Daniels, Stephen; Lucas, Olabanji; Mitra, Anirban; Martinez-Rosas, Miguel; Reader, Alec; Cameron, David C. (My University, 2005)
γ-CuCl is a wide-bandgap (Eg = 3.395eV), direct bandgap, semiconductor material with a cubic zincblende lattice structure. Its lattice constant, aCuCl = 0.541 nm, means that the lattice mismatch to Si (aSi = 0.543 nm) is <0.5%. γ-CuCl on Si-the growth of a wide-bandgap, direct bandgap, optoelectronics material on silicon substrates is a novel material system, with compatibility to current Si based electronic/optoelectronics technologies. The authors report on early investigations consisting of the growth of polycrystalline, CuCl thin films on Si (100), Si (111), and quartz substrates by physical vapour deposition. X-ray diffraction (XRD) studies indicate that CuCl grows preferentially in the <111> direction. Photoluminescence (PL) and Cathodoluminescence (CL) reveal a strong room temperature Z3 excitonic emission at ~387nm. A demonstration electroluminescent device (ELD) structure based on the deposition of CuCl on Si was developed. Preliminary electroluminescence measurements confirm UV light emission at wavelengths of ~380nm and ~387nm, due to excitonic behaviour. A further emission occurs in the bandgap region at ~360nm.
Proceedings of SPIE, Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
SPIE Opto-Ireland 2005
Keywords: Copper chloride; Wide-bandgap semiconductor; Ultra-violet; Silicon; Electroluminescence; Cathodoluminescence; Photoluminescence; Exciton